(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article analyzes optic nerve atrophy resulting from increased intraocular pressure (IOP) and its role in the pathogenesis of glaucoma. Glaucoma is considered the most common cause of irreversible blindness worldwide. Studies show that elevated IOP leads to mechanical compression at the optic nerve head, impaired blood circulation, and neurodegenerative processes that result in the loss of retinal ganglion cells. This paper discusses the pathophysiological mechanisms of the disease, diagnostic methods, and modern neuroprotective approaches. The aim of this article is to scientifically analyze the role of optic nerve atrophy caused by elevated IOP in the development of glaucoma, to highlight its pathogenetic mechanisms, and to review modern diagnostic and therapeutic strategies.